Actigraphic multi‐night home‐recorded sleep estimates reveal three types of sleep misperception in Insomnia Disorder and good sleepers. (31st October 2019) - te Lindert, Bart H. W.; Blanken, Tessa F.; van der Meijden, Wisse P.; Dekker, Kim; Wassing, Rick; van der Werf, Ysbrand D.; Ramautar, Jennifer R.; Van Someren, Eus J. W.
Abstract: People with Insomnia Disorder tend to underestimate their sleep compared with polysomnography or actigraphy, a phenomenon known as paradoxical insomnia or sleep‐state misperception. Previous studies suggested that night‐to‐night variability could be an important feature differentiating subtypes of misperception. This study aimed for a data‐driven definition of misperception subtypes revealed by multiple sleep features including night‐to‐night variability. We assessed features describing the mean and dispersion of misperception and objective and subjective sleep duration from 7‐night diary and actigraphy recordings of 181 people with Insomnia Disorder and 55 people without sleep complaints. A minimally collinear subset of features was submitted to latent class analysis for data‐driven subtyping. Analysis revealed three subtypes, best discriminated by three of five selected features: an individual's shortest reported subjective sleep duration; and the mean and standard deviation of misperception. These features were on average 5.4, −0.0 and 0.5 hr in one subtype accommodating the majority of good sleepers; 4.1, −1.4 and 1.0 hr in a second subtype representing the majority of people with Insomnia Disorder; and 1.7, −2.2 and 1.5 hr in a third subtype representing a quarter of people with Insomnia Disorder and hardly any good sleepers. Subtypes did not differ on an individual's objective sleep duration mean (6.9, 7.2 and 6.9 hr) and standard deviation (0.8, 0.8 and 0.9 hr). Data‐driven analysis of naturalistic sleep revealed three subtypes that markedly differed in misperception features. Future studies may include misperception subtype to investigate whether it contributes to the unexplained considerable individual variability in treatment response.